Various-sized Municipalities Dealing with Growth Issues:: Different Issues but the Same Solutions? - Brorström, Sara; Parment, Anders (Scandinavian Journal of Public Administration, 2016)
This article deals with differences in identified growth issues between areas, ranging from managing growth in metropolitan areas to managing decreasing population in rural areas. Across areas, attempts are made to realize and communicate shared visions of place; however, because inhabitants may not agree with these attempts, confusion rather than the intended outcomes may result. Pressure to grow tends to result in resources being spent on branding activities with limited results, and populations continue to decline in rural areas despite such efforts. Growth may cause problems unless it is managed in harmony with the place identity, so ensuring that the local community supports branding efforts is crucial, quite apart from the fact that growth per se may not automatically increase place attractiveness. Our research questions the dominant paradigm suggesting that economic growth is the key driver of place attractiveness and success. We also draw parallels to the sustainability concept to highlight different perspectives of population growth.